Antioxidant, Antibacterial and Anti-cancer Properties of Bio -fabricated Copper-silver-zinc Nanocomposites: An Ecofriendly Approach - Kavipriya, Madeswaran; Selleswari, Dhanasekaran; Unnimaya, Unnikumar; J. R., Retheesh Kumar Sreedevi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Recent advancements in nanotechnology have led to the development of bio-fabricated copper-silver-zinc nanocomposites, which exhibit multifunctional properties suitable for various applications. This study investigates their antioxidant, antibacterial, anti-cancer, and conductive properties through an eco-friendly synthesis approach. The nanocomposites were synthesized using Allium sativum extracts as reducing agents, ensuring minimal environmental impact and promoting sustainability. Antioxidant activities were evaluated using DPPH and ABTS, FRAP, Phosphomolybdenum and superoxide assays, demonstrating significant scavenging capabilities comparable to standard antioxidants. Antibacterial efficacy was assessed against Gram-negative bacteria, E. coli revealing potent inhibitory effects attributed to the synergistic action of copper, silver, and zinc nanocomposites (Cu-Ag-Zn-NC). Furthermore, the nanocomposites exhibited promising anticancer activity against breast cancer cells MCF-7, highlighting their potential as therapeutic agents. Electrical conductivity measurements confirmed their suitability for use in electronic applications, underscoring their versatility. This study underscores the eco-friendly synthesis of bio-fabricated copper-silver-zinc nanocomposites and their multifaceted properties, positioning them as promising candidates for biomedical, environmental, and technological applications.